2018
DOI: 10.1186/s40066-017-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability on household food availability in Tigray, Ethiopia

Abstract: Background: Currently, climate variability is a hot issue across the globe, especially in countries where rain-fed agriculture is a means of livelihood. Climate variability increases the risks of hunger in the region as it affects all four components of food security: food availability, food accessibility, food utilization and food stability. Rainfall shortage or excess hampers food production in the region, causing food insecurity and escalating famine. Extreme weather is affecting people indirectly through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…Our results indicate that farmers who are more educated would be more productive and efficient, and eventually, they would generate more farm income and overcome their poverty as compared to the less educated ones, and this argument is in line with the findings of other relevant studies [e.g. 23,37,51,[54][55][56].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results indicate that farmers who are more educated would be more productive and efficient, and eventually, they would generate more farm income and overcome their poverty as compared to the less educated ones, and this argument is in line with the findings of other relevant studies [e.g. 23,37,51,[54][55][56].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been observed for the case of total land for per capita income of headcount for both categories of farmers i.e. adapters and non-adapters, and through this finding our study validate the outcomes of a similar study by [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Determinants of different adaptation strategies and their impact on food security and poverty level were quantified by References [35,42]. The impact of CC was assessed by Reference [43] on the food security of rural households. Results of the food balance model showed that more than 80% of rural households were food-insecure due to CC.…”
Section: Introductionmentioning
confidence: 99%
“…Climate is an important resource both for crop and livestock productions in developing regions as farmers depend largely on rain fed agriculture (Birara et al., 2015; Coulibaly, 2015). However, keeping all other factors constant, climatic change could decline yield and reducing the availability of foods which aggravates household food insecurity (Butt et al., 2005; Weldearegay & Tedla, 2018). Growing consensus in the scientific community also indicates that higher temperature and changing precipitation levels resulting from climate change which reduces crop yields in developing countries (Alemu & Mengistu, 2019).…”
Section: Introductionmentioning
confidence: 99%